Multiliteracies Pedagogy In Raising Gender Awareness Through Sue Monk Kidd’s The Secret Life Of Bees - Laili, Muawwinatul (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2023)
ABSTRACT The purpose of this study is to investigate the implementation of the Multiliteracy Pedagogy approach promoted by the New London Group (1996) in raising gender awareness through The Secret Life of Bees movie, which was adapted from Sue Monk Kidd's novel of the same name (2001). The participants of this research are seventeen fifth semester English Education students and an English lecturer. Using qualitative data from observation and an online questionnaire. The findings revealed that through The Secret Life of Bees, the four elements of Multiliteracies Pedagogy are well implemented in the classroom, which in turn could raise the students’ awareness in relation to gender issues. The learning activities in each element of multiliteracies pedagogy provides the students not only the situation to experience the issue but also the discussion and other learning activities which invite them to critically explore their ideas about gender issues. It shows that multiliteracies pedagogy which is meaningful in raising gender awareness. The students give positive responses toward the use of multiliteracies pedagogy to raise gender awareness as seen from the result of the questionnaire that the students are excited, comfortable, and confident in sharing their critical ideas regarding gender issues after watching the movie. KEYWORDS: Multiliteracy Pedagogy; Gender Awareness; The Secret Life of Bees   ABSTRAK Dalam proses pembelajaran pendidik seharusnya dapat membawa karya sastra sebagai materi ajar yang disesuaikan dengan konsep pengajaran abad ke 21. Penerapan pendekatan Pedagogi Multiliterasi (Multiliteracies Pedagogy) yang digagas pertama kali oleh New London Group (1996) melalui film The Secret Life of Bees  untuk membangun kesadaran gender yang diadopsi dari sebuah novel dengan judul yang sama karya Sue Monk Kidd (2001). Subjek penelitian ini adalah tujuh belas mahasiswa semester lima pada program studi Pendidikan Bahasa Inggris. Peneliti menggunakan metode kualitatif untuk menganalisis data hasil observasi dan kuesioner. Peneliti menerapkan pendekatan Multiliteracies Pedagogy yang terdiri dari empat aspek, yaitu; a) situated practice, b) overt instruction, c) critical framing, dan d) transformed practice. Hasil penelitian memperlihatkan aktifitas pembelajaran yang merefleksikan empat aspek pedagogi multiliterasi  tersebut dalam membangun kesadaran gender menggunakan film The Secret Life of Bees. Selain itu, mahasiswa memberikan respon positif terkait penggunaan pedagogi multiliterasi untuk membangun kesadaran gender melalui film The Secret Life of Bees. Kata Kunci: Pedagogi Multiliterasi, Kesadaran Gender, The Secret Life of Bees